The value of the scholarly-led, non-profit business model to achieve Open Access and scholarly publishing beyond APC: AmeliCA’s cooperative approach - Becerril-García, Arianna (Septentrio Conference Series, 2019)
Watch the VIDEO. Keynote presentation. The prevailing science communication system has showed little success in making science a global, participatory and equitable conversation. At the same time, a very robust ecosystem of science communication has been built in the Latin-American region, one that is intrinsically open, non-commercial and academy-owned. However, this “regional” approach has remained outside the legitimated channels of scholarly communication. In Latin America, more than 2000 universities are publishing journals under the principle of science as a common and public good. Around half of them are public institutions which means that public budget is being heavily invested in sustaining non-commercial Open Access. AmeliCA, a multi-institutional community-driven initiative supported by UNESCO and led by Redalyc and CLACSO, seeks a cooperative, sustainable, protected and non-commercial solution for Open Knowledge. AmeliCA is taking the 16-year experience and technological resources from Redalyc to strengthen non-profit publishing beyond the region. AmeliCA’s and Redalyc’s approach is based on the fact that scholarly communication in control of the academy is a strategy much healthier and sustainable for the development of science and society. Why is it that commercial publishers are a pivotal actor in science communication – in many parts of the world – if the biggest part of activities concerning the generation of knowledge is in the academy? Academy owned publishing seems not to exist in the mainstream databases (Web of Science and Scopus). So, it is strategic for the research community and libraries to join forces, as well as share and connect individual efforts to build a cooperative infrastructure, in order to guarantee that publishing is led by the scholarly community and that its openness is sustainable. The research community and libraries should also work together in the reshaping of how research is assessed, in order to give the non-profit academy-owned scholarly communications their place. All must be leveraged with technology to find more effective methods of communication and deployment of the knowledge generated by different regions, disciplinary fields or languages.